10 Critical Considerations When Developing an AI. (8th May 2020) - Oatridge, Nic
Abstract: Concerns about the dangers of AI are older than the field itself, dating at least as far back as Isaac Asimov's 1942 Three Laws of Robotics, writes Nic Oatridge MSc MBCS.